Battery cell wettability testing method
Patent Information
- Application Number
- CN202411477035.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-02-11
AI Technical Summary
The prior art is difficult to accurately evaluate the wetting properties of lithium-ion battery cells, resulting in insufficient or excessive wetting in actual production, affecting battery performance and safety.
Changes in the properties of the electrolyte are detected to evaluate the wettability of the battery cell by adding indicators to the battery slurry, injecting the electrolyte and leaving it stand.
This method can accurately and easily evaluate the wetting properties of the battery cell, which is simple to operate, low cost, strong applicability, and will not affect the wetting process of the battery cell, improving the accuracy and reliability of the detection.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a method for testing the wettability of a battery cell. Background Art
[0002] Lithium-ion batteries have been increasingly widely used in mobile phones, computers, tablets, Bluetooth headsets, power tools, automobiles, energy storage and other fields. The market has put forward higher requirements for the energy density and safety performance of lithium batteries. In order to develop lithium-ion batteries with higher energy density and better safety performance, researchers have increased the surface density and compaction density of the pole piece, increased the shell ratio of the battery cell, and made larger battery cells, which is currently a common solution to increase battery energy density. However, the increase in surface density and compaction density also causes the wettability of the electrolyte on the pole piece to decrease, hindering the shuttle of lithium ions between the positive and negative electrodes, and increasing the interface impedance; the increase in the shell ratio makes the stress between the pole piece and the diaphragm greater, and it is more difficult for the electrolyte to enter the pole piece and the diaphragm, resulting in the situation that the pole piece is only partially completely infiltrated with the electrolyte; therefore, in actual production, it is often necessary to quantitatively evaluate the wettability of the diaphragm.
[0003] The current methods used to judge wetting, such as contact angle measurement and capillary glass tube method, are based on the interaction between the electrolyte and the electrode surface. However, in the actual production process, there will be positive and negative pressures of the equipment to assist, and it is impossible to judge the true wetting of the electrode in the battery cell, which is inconsistent with the actual production. Because after the positive and negative pressure cycles of the equipment, the electrolyte is basically covered on the surface of the electrode. For wetting, the process from the surface of the electrode to the part close to the foil is difficult. Methods such as adding luminescent materials require the battery cell to be disassembled to observe the luminescence and then judge the wetting situation. In the process of disassembling the battery cell, it is easy to cause changes in the wetting situation, which is greatly affected by random factors, resulting in low accuracy of the measurement results. High-tech technologies such as ultrasound, X-ray detection, and CT scanning are not applicable due to the inconvenience of testing caused by equipment limitations and high testing costs.
[0004] Based on this, it is urgent to invent a battery cell wettability testing method to solve the above-mentioned technical problems. Summary of the invention
[0005] One of the purposes of the present invention is to provide a battery cell wettability testing method to address the deficiencies in the prior art, which can measure the wettability of the battery cell in the actual production process, has simple operation, good accuracy, low cost and strong applicability.
[0006] To achieve the above objectives, this application adopts the following technical solutions:
[0007] A method for testing the wettability of a battery cell is provided, comprising the following steps:
[0008] S1. Adding an indicator to the battery slurry, wherein the indicator is soluble in the electrolyte, and preparing a battery cell to be tested according to the slurry;
[0009] S2, injecting the electrolyte into the battery cell to be tested, and leaving the battery cell to be tested still;
[0010] S3. Detecting changes in the properties of the electrolyte, and characterizing the wettability of the battery cell according to the changes in the properties of the electrolyte and the standing time.
[0011] Specifically, the indicator in step S1 is a dye, and step S3 is to detect the color change of the electrolyte, and judge the wettability of the battery cell according to the color change of the electrolyte and the standing time.
[0012] Specifically, the dye is one or more of an oil-soluble dye, an oil-soluble toner, and an oil-soluble fluorescent dye.
[0013] Specifically, the mass ratio of the dye to the battery slurry is (0.05-0.5):100.
[0014] Specifically, the electrolyte is colorless and transparent.
[0015] Specifically, the electrolyte contains one or more of cyclic carbonate, linear carbonate, carboxylic acid ester, lithium salt, vinylene carbonate and carbonate sulfate.
[0016] Specifically, the mass ratio of cyclic carbonate and co-solvent in the electrolyte is (10-40): (60-90), wherein the co-solvent is linear carbonate and / or carboxylate, the amount of lithium salt is 0.5M-1.5M, and the mass proportion of the additive in the electrolyte is 0.5%-5%.
[0017] Specifically, the standing temperature is between 20°C and 80°C.
[0018] Specifically, the standing temperature is between 45°C and 65°C.
[0019] Specifically, in step S3, the infiltration speed of the battery cell is characterized according to the ratio of the property change of the electrolyte and the standing time.
[0020] The beneficial effects of the present invention are as follows: the present application judges the infiltration of the battery cell by the electrolyte by the change of the properties of the electrolyte caused by the dissolution of the indicator in the battery cell, which is consistent with the infiltration of the battery cell by the electrolyte in the actual production process, and the judgment of the infiltration of the battery cell is made by judging the change of the properties of the electrolyte, which will not affect the infiltration of the battery cell and cause the deviation of the detection result, and can be more accurate and quantitative analysis can be performed. DETAILED DESCRIPTION
[0021] The technical solutions in the embodiments of the present application will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by technicians in the technical field of the present application. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application.
[0022] In the battery manufacturing process, after the electrolyte is injected, it needs to be left to stand for a period of time to ensure that the pole piece and the diaphragm are fully infiltrated before the subsequent battery formation steps can be carried out. Insufficient infiltration during the battery formation will lead to problems such as black spot lithium precipitation, which will cause battery performance degradation and safety risks; too long infiltration time will extend the battery production cycle and increase the battery manufacturing cost. Therefore, how to accurately test the electrolyte infiltration rate and battery infiltration condition of the battery has become an urgent technical problem to be solved in current battery research.
[0023] In the existing technology, the test methods for battery wetting include contact angle measurement, capillary glass tube method, etc. These methods are judged by the interaction between the electrolyte and the electrode surface, but in the actual production process, there will be positive and negative pressure of the equipment to assist, and it is impossible to judge the real wetting of the electrode in the battery cell, which is inconsistent with the actual production. Because after the positive and negative pressure of the equipment is circulated, the electrolyte is basically covered on the surface of the electrode. For wetting, the process from the surface of the electrode to the part close to the foil is difficult. The method of adding luminescent materials is to judge the wetting condition by the distribution of luminescent materials in the cross-section of the battery cell after cutting. Since the battery cell needs to be cut to observe the luminescence and then judge the wetting condition, and the wetting condition is easily changed during the process of cutting the battery cell, it is greatly affected by random factors, resulting in low accuracy of the measurement results; and high-tech technologies such as ultrasonic, X-ray detection, and CT scanning are not applicable due to the inconvenience of testing caused by equipment limitations and high testing costs.
[0024] In the present application, by adding an indicator to the battery slurry, the method of directly detecting the wettability of the battery cell in the prior art is changed to indirectly detecting the wettability of the battery cell by detecting the electrolyte. Since the wettability of the battery cell is detected by detecting the electrolyte, detecting the electrolyte will not affect the wetting effect of the battery cell during detection, which is closer to the actual process of battery cell wetting. In addition, compared with directly detecting the battery cell, the method of detecting the indicator in the electrolyte is simpler.
[0025] Example 1
[0026] This embodiment provides a method for testing the wettability of a battery cell, comprising the following steps:
[0027] S1. Add an indicator into the battery slurry, where the indicator is soluble in the electrolyte, and prepare a battery cell to be tested according to the slurry;
[0028] S2, injecting electrolyte into the battery cell to be tested, and leaving the battery cell to be tested still;
[0029] S3. Detect changes in the properties of the electrolyte, and characterize the wettability of the battery cell based on the changes in the properties of the electrolyte and the standing time.
[0030] The purpose of adding an indicator to the battery slurry in the present application is that when the electrolyte infiltrates the battery cell, the indicator dissolves in the electrolyte causing the properties of the electrolyte to change. This change can provide an indication of the wetting of the battery cell, and the wettability of the battery cell can be judged by the amount of indicator dissolved in the electrolyte. In order to achieve this purpose, the indicator needs to be evenly distributed in the battery cell so that each part of the battery cell has the same impact on the electrolyte when it is infiltrated by the electrolyte and has the same indication effect. Therefore, the present application adds the indicator during the stirring of the battery slurry, and stirs it sufficiently after adding the indicator to avoid precipitation or aggregation of the indicator, thereby ensuring that the indicator can be evenly distributed in the battery cell. Before actual application, experiments are required to verify that the battery cell prepared with the stirred slurry can provide consistent wetting indications in all parts. Ensuring uniform distribution and sufficient stirring of the indicator is the key to achieving accurate detection, which can effectively improve the reliability of detecting the wettability of the battery cell.
[0031] There are no special requirements for the preparation process of the battery cell to be tested. In order to prevent different preparation processes from causing different wetting effects of the battery cells, the production of the battery cell to be tested is carried out according to the conventional battery cell production process.
[0032] When judging the wettability of a battery cell, a standard battery cell can be first selected as a reference example of complete wetting, and the standard battery cell can be soaked for a long time until the properties of the electrolyte do not change, ensuring that the wetting state of the standard battery cell meets the ideal complete wetting standard, and detecting the property changes of the electrolyte of the reference example. The property changes of the electrolyte of the reference example can be used as a reference to evaluate the wetting of the battery cell to be tested. At different standing time points, the property changes of the electrolyte in the battery cell to be tested are measured. The wettability of the battery cell under different standing conditions can be compared based on the property changes of the electrolyte and the standing time. The battery cell wettability detection method can effectively evaluate the wettability of the battery cell, and the detection process is consistent with the actual production process and will not affect the accuracy and reliability of the test results. The detection method can accurately find the best standing conditions, shorten the wetting time while ensuring the wettability of the battery cell, reduce the battery production cycle, and improve the battery production efficiency.
[0033] In some embodiments, the ratio of the change in the property of the electrolyte and the standing time is used to characterize the wetting speed of the battery cell. Since the infiltration of the electrolyte is proportional to the change in the property of the electrolyte, the wetting speed of the battery cell can be characterized by the ratio of the change in the property of the electrolyte and the standing time. Since there may be a nonlinear relationship between the change in the property of different electrolytes and the wetting process, the direct use of the ratio may not be accurate enough. Therefore, it is necessary to convert or adjust to obtain an accurate wetting speed. Experiments are conducted to obtain a relationship curve between the change in the property of the electrolyte and the standing time, and the nonlinear relationship is determined by fitting the curve. Based on the fitting results, a conversion formula is established to convert the measured property changes and standing time into a standardized wetting speed index. For example, the formula obtained by regression analysis is used to correct the ratio so that it can accurately reflect the wetting speed. In this way, the wetting speed of the battery cell can be effectively characterized, and it is suitable for comparison and analysis of different electrolytes.
[0034] Example 2
[0035] The difference from Example 1 is that in this embodiment, the indicator in step S1 is a dye, and step S3 is to detect the color change of the electrolyte, and the wettability of the battery cell is determined according to the color change of the electrolyte and the standing time.
[0036] The indicator is set as a dye and the wettability of the battery cell is judged according to the chromaticity change of the electrolyte. Since the color change is intuitively reflected in the electrolyte, a preliminary judgment on the wettability of the electrolyte can be achieved by the human eye only without a detection instrument. It is suitable for preliminary screening, especially in rapid evaluation and on-site operation. After preliminary screening to the static conditions within the appropriate range, the chromaticity of the electrolyte under the static conditions within the range is detected by the instrument to find the best static conditions. In some embodiments, when the accuracy requirement for the chromaticity is low, it is also possible to choose to judge the chromaticity of the electrolyte only by the human eye using a colorimetric card to reduce costs.
[0037] Preferably, the dye is one or more of an oil-soluble dye, an oil-soluble color powder, and an oil-soluble fluorescent dye, because they can provide clear and stable color changes in the electrolyte, thereby helping to accurately judge the wettability of the battery cell. These dyes can ensure that the color changes are obvious and easy to identify with the naked eye, and are suitable for rapid screening and preliminary evaluation. The selection of dyes needs to be based on the type of electrolyte and the static conditions. It is necessary to ensure that there is no reaction between the dye and the electrolyte and between the dye and the battery slurry, and the dye is not easy to change color under the static environment of the electrolyte, ensure the stability of the color change, and ensure that the color change of the electrolyte is only affected by the dissolution of the dye in the electrolyte during infiltration.
[0038] Preferably, the mass ratio of the dye to the battery slurry is (0.05-0.5):100. When testing the wettability of the battery cell, it is necessary to ensure that the wettability of the battery cell does not change after the addition of the dye. Therefore, the mass ratio of the dye in the battery slurry cannot be too high, and the selected dye concentration needs to ensure that the chromaticity of the electrolyte can be significantly changed without significantly affecting the battery performance, so as to prevent the chromaticity change from being too small to cause errors in chromaticity detection. Within the above-mentioned range of the present application, the concentration of the dye in the battery slurry is ensured to be low enough to prevent a significant impact on the wettability of the battery cell, and at the same time high enough to allow the color change of the dye to be clearly observed.
[0039] Preferably, the electrolyte is colorless and transparent, because this can ensure that the color change of the dye is more obvious and easy to observe. The colorless and transparent electrolyte will not interfere with the chromaticity change of the dye, making the wettability test results more accurate and intuitive.
[0040] Preferably, the electrolyte contains one or more of cyclic carbonates, linear carbonates, carboxylates, lithium salts, vinylene carbonate and carbonate sulfate.
[0041] Specifically, the mass ratio of cyclic carbonate and co-solvent in the electrolyte is (10-40): (60-90), wherein the co-solvent is linear carbonate and / or carboxylate, the amount of lithium salt is 0.5M-1.5M, and the mass proportion of the additive in the electrolyte is 0.5%-5%.
[0042] Preferably, the standing temperature is between 20° C. and 80° C., within which the electrolyte will not be damaged, and the electrolyte can be prevented from decomposing or reacting due to excessively high temperature.
[0043] More preferably, the standing temperature is between 45° C. and 65° C., within which the electrolyte will not change color, or the color change is so small that it will not affect the chromaticity judgment of the electrolyte.
[0044] Example 3
[0045] A method for judging the quality of electrode wetting in a large battery cell comprises the following steps: according to the amount of positive electrode material, 0.2% by mass of orange oily toner is added before coating, slowly stirred for half an hour under vacuum conditions, and then the slurry is coated normally and then roller pressed (the compacted density of the positive electrode powder is 2.4g / cm 3 ), slitting, die-cutting, winding and assembling with matching negative electrodes, baking and injecting the obtained battery cells, standing the injected battery cells in an oven at 45°C for 3 hours, disassembling the battery cells, obtaining the electrolyte containing ink and conducting colorimetry test and electrolyte composition analysis, and taking 3 parallel samples to obtain the average value.
[0046] Example 4
[0047] The difference from Example 3 is that the battery cell after liquid injection is left to stand in an oven at 45° C. for 6 hours.
[0048] The rest is the same as in Example 1 and will not be described again here.
[0049] Example 5
[0050] The difference from Example 3 is that the battery cell after liquid injection is left to stand in an oven at 45° C. for 9 hours.
[0051] The rest is the same as in Example 1 and will not be described again here.
[0052] Example 6
[0053] The difference from Example 3 is that the battery cell after liquid injection is left to stand in an oven at 45° C. for 12 hours.
[0054] The rest is the same as in Example 1 and will not be described again here.
[0055] Example 7
[0056] The difference from Example 3 is that the battery cell after liquid injection is left to stand in an oven at 45° C. for 15 hours.
[0057] The rest is the same as in Example 1 and will not be described again here.
[0058] Example 8
[0059] The difference from Example 3 is that the battery cell after liquid injection is left to stand in an oven at 55° C. for 6 hours.
[0060] The rest is the same as in Example 1 and will not be described again here.
[0061] Example 9
[0062] The difference from Example 3 is that the battery cell after liquid injection is left to stand in an oven at 65° C. for 6 hours.
[0063] The rest is the same as in Example 1 and will not be described again here.
[0064] Example 10
[0065] The difference from Example 3 is that the compaction density of the positive electrode powder is 2.55 g / cm 3 The battery cell after injection was placed in an oven at 45°C for 6 hours.
[0066] The rest is the same as in Example 1 and will not be described again here.
[0067] Embodiment 11
[0068] The difference from Example 3 is that the compaction density of the positive electrode powder is 2.55 g / cm 3 The battery cell after injection is placed in an oven at 45°C for 24 hours.
[0069] The rest is the same as in Example 1 and will not be described again here.
[0070] Comparative Example 1
[0071] A method for judging the quality of electrode wetting in a large battery cell, the method comprising the following steps:
[0072] According to the amount of positive electrode material, add 0.2% orange oily color powder by mass before coating, stir slowly for half an hour under vacuum conditions, then coat the slurry normally and then roll it (the compaction of the positive electrode powder is 2.4g / cm 3 ), slitting, die-cutting, winding and assembling with matching negative electrodes, baking and injecting the obtained battery cells, without standing the battery cells after injection, disassembling the battery cells after injection, obtaining the electrolyte containing ink and performing colorimetry test and electrolyte composition analysis, and taking 3 parallel samples to obtain the average value.
[0073] Comparative Example 2
[0074] A method for judging the quality of electrode wetting in a large battery cell, the method comprising the following steps:
[0075] According to the amount of positive electrode material, add 0.2% orange oily color powder by mass before coating, stir slowly for half an hour under vacuum conditions, then coat the slurry normally and then roll it (the compaction of the positive electrode powder is 2.4g / cm 3 ), slitting, die-cutting, winding and assembling with matching negative electrodes, baking and injecting the obtained battery cells, leaving the injected battery cells in an oven at 45°C for 72 hours, disassembling the battery cells, obtaining the electrolyte containing ink and conducting colorimetry test and electrolyte composition analysis, and taking 3 parallel samples to obtain the average value.
[0076] Electrolyte color detection
[0077] Take a sample from the electrolyte containing the ink and to ensure the sample is representative, measure the color of the electrolyte using a colorimeter or spectrophotometer.
[0078] Electrolyte composition analysis
[0079] The composition of the electrolyte containing ink is compared with that of the original formula electrolyte injected into the battery cell. When there is no obvious change compared with the original formula, it means that the electrolyte has not reacted during the static process to cause a color change, and the color change of the electrolyte is only affected by the dissolution of the dye.
[0080] The test results are shown in Table 1
[0081] Table 1
[0082] Group Chroma / Hazen Electrolyte composition analysis Example 3 233 No significant changes compared to the original formula Example 4 341 No significant changes compared to the original formula Example 5 391 No significant changes compared to the original formula Example 6 471 No significant changes compared to the original formula Example 7 473 No significant changes compared to the original formula Example 8 442 No significant changes compared to the original formula Example 9 475 No significant changes compared to the original formula Example 10 207 No significant changes compared to the original formula Embodiment 11 467 No significant changes compared to the original formula Comparative Example 1 40 No significant changes compared to the original formula Comparative Example 2 476 No significant changes compared to the original formula
[0083] By comparing Examples 3-7 with Comparative Examples 1 and 2, it can be seen that the chromaticity of the electrolyte increases with the increase of the standing time. The increase in the chromaticity of the electrolyte is due to the infiltration of the electrolyte into the battery cell to dissolve the dye. Therefore, the infiltration effect under different standing times can be evaluated by the size of the chromaticity.
[0084] From the comparison of Examples 4, 8 and 9, it can be seen that when the standing temperature rises, the chromaticity of the electrolyte changes more greatly at the same standing time. The method of the present application can evaluate the wetting effect of the battery cell at different temperatures for the same time.
[0085] From the comparison of Examples 4, 10, and 11, it can be seen that when the compaction density of the positive electrode increases, the wetting effect decreases, and the chromaticity of the electrolyte changes little. The present application can evaluate the wetting effect of battery cells with different compaction densities by the size of the chromaticity, and improve the wetting effect of battery cells with high compaction density by increasing the wetting time and increasing the temperature, and use the method of the present application to evaluate the wetting effect.
[0086] From the above, it can be seen that the method of the present application can evaluate the wetting effect of actual battery cells, which is beneficial to the evaluation of actual production.
[0087] The above description shows and describes several preferred embodiments of the present invention, but as before, it should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the invention concept of this article through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art do not depart from the spirit and scope of the present invention, and should be within the scope of protection of the claims attached to the present invention.
Claims
1. A method for testing the wettability of a battery cell, characterized in that: The following steps are involved: S1. Adding an indicator to the battery slurry, wherein the indicator is soluble in the electrolyte, and preparing a battery cell to be tested according to the slurry; S2, injecting the electrolyte into the battery cell to be tested, and leaving the battery cell to be tested still; S3. Detecting changes in the properties of the electrolyte, and characterizing the wettability of the battery cell according to the changes in the properties of the electrolyte and the standing time.
2. The method for testing the wettability of a battery cell according to claim 1, characterized in that: The indicator in step S1 is a dye, and step S3 is to detect the color change of the electrolyte, and judge the wettability of the battery cell according to the color change of the electrolyte and the standing time.
3. The method for testing the wettability of a battery cell according to claim 2, characterized in that: The dye is one or more of an oil-soluble dye, an oil-soluble toner and an oil-soluble fluorescent dye.
4. The method for testing the wettability of a battery cell according to claim 2, characterized in that: The mass ratio of the dye to the battery slurry is (0.05-0.5):
100.
5. The method for testing the wettability of a battery cell according to claim 2, characterized in that: The electrolyte is colorless and transparent.
6. The method for testing the wettability of a battery cell according to claim 5, characterized in that: The electrolyte contains one or more of cyclic carbonate, linear carbonate, carboxylic acid ester, lithium salt, vinylene carbonate and carbonate sulfate.
7. The method for testing the wettability of a battery cell according to claim 6, characterized in that: The mass ratio of cyclic carbonate to co-solvent in the electrolyte is (10-40): (60-90), wherein the co-solvent is linear carbonate and / or carboxylate, the amount of lithium salt is 0.5M-1.5M, and the mass proportion of the additive in the electrolyte is 0.5%-5%.
8. The method for testing the wettability of a battery cell according to claim 1, characterized in that: The standing temperature is between 20℃-80℃.
9. The method for testing the wettability of a battery cell according to claim 8, characterized in that: The standing temperature is between 45°C and 65°C.
10. The method for testing the wettability of a battery cell according to claim 1, characterized in that: In the step S3, the infiltration speed of the battery cell is characterized according to the ratio of the property change of the electrolyte and the standing time.